2020
DOI: 10.3390/jmse8020083
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Random Access Algorithm for Very High Frequency Data Exchange (VDE)

Abstract: VHF Data Exchange System (VDES) is considered as an important component of the future maritime communication system by the International Maritime Organization (IMO). On the basis of the existing Automatic Identification System (AIS), VDES adds the other two higher capacity subsystems: Application Specific Message (ASM) and VHF Data Exchange (VDE). The Random Access Channel (RACH) of VDE was first introduced in the International Telecommunication Union (ITU) Recommendation M.2092-0. As the slot planning princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…One of the systems that can serve to modernize GMDSS, if included in its infrastructure, is the VHF Data Exchange System (VDES), which was developed as a direct response to congestion of Automatic Identification System (AIS) [19][20][21][22]. Namely, a study conducted in 2013 by the International Telecommunication Union (ITU) has proved that in some parts of the world with dense maritime traffic, a limit of 50% of the data link capacity, which represents the critical level of the ship's AIS station, has been reached [23].…”
Section: Discussionmentioning
confidence: 99%
“…One of the systems that can serve to modernize GMDSS, if included in its infrastructure, is the VHF Data Exchange System (VDES), which was developed as a direct response to congestion of Automatic Identification System (AIS) [19][20][21][22]. Namely, a study conducted in 2013 by the International Telecommunication Union (ITU) has proved that in some parts of the world with dense maritime traffic, a limit of 50% of the data link capacity, which represents the critical level of the ship's AIS station, has been reached [23].…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that a competitive Random-Access Channel (RACH) procedure employed by the system leads to a significant efficiency loss and an aggregated throughput degradation in the case of a high number of VDES terminals attempting to transmit data. A study of the effect is presented in [83], where authors analyze the RACH algorithm efficiency in detail.…”
Section: A Scalability Of Local Area Maritime Servicesmentioning
confidence: 99%
“…It achieves maximum throughput up to 10 times higher than that of the traditional asynchronous pure Aloha (PA) protocol in a single channel. In addition, a novel random access algorithm called adaptive traffic load contention resolution diversity slotted ALOHA (ATL-CRDSA) was proposed in Jiang's study (Jiang et al., 2020). Unlike the VDE slot map and continuous slot map given by ITU, ATL-CRDSA combines the load control strategy with contention resolution to overcome the challenges in the random access channel of VDE.…”
Section: Related Workmentioning
confidence: 99%